The efficacy and safety of levofloxacin 750 mg (Hileflox) in the treatment of chronic prostatitis - L. A. Logvinov; K. V. Kumachev; I. V. Vinogradov; L. M. Vinogradova; M. Yu. Gabliya; E. S. Dendeberov (Андрология и генитальная хирургия, 2014)
Chronic prostatitis is the most common urological disease in men aged 20 to 50 years. Chronic bacterial prostatitis occurs in 5–10 % of cases.The aim of the study was to determine the efficacy and safety of Hileflox (levofloxacin) in chronic bacterial prostatitis in a dosage of 750 mg per day for 10 days. The study involved 40 patients with chronic bacterial prostatitis.Results. National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) scores were decreased by 72 %, which is characterized as a distinct clinical effect. Quality of life has changed on average from 4.64 to 1.46 points, which was 68 %. Results of uroflowmetry before and after treatment showed a positive trend. According to the benchmark survey of microbiological eradication of the pathogen was found in 36 (90 %) patients. In 4 patients was recorded persistence of previously identified pathogens in diagnostically significant titre. Side effects were observed in 3 (7.5 %) patients. Hileflox (levofloxacin) 750 mg course of 10 days showed marked clinical (87.5 %) and bacterial (90 %) effective in chronic bacterial prostatitis. Necessary to conduct further analysis to determine the duration of relapse-free interval.